2022
DOI: 10.1002/smll.202204155
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Coordination‐Pairing between Ru Clusters and Single‐Atoms for Efficient Hydrogen Evolution Reaction in Alkaline Seawater

Abstract: The coordination environment of Ru centers determines their catalytic performance, however, much less attention is focused on cluster‐induced charge transfer in a Ru single‐atom system. Herein, by density functional theory (DFT) calculations, a competitive coordination‐pairing between Ru clusters (RuRu bond) and single‐atoms (RuO bond) is revealed leading to the charge redistribution between Ru and O atoms in ZnFe2O4 units which share more free electrons to participate in the hydrogen desorption process, opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…23,24 Cl − deposition on the cathode surface leads to poor electrode stability and the inferior efficiency of the catalyst. [25][26][27][28] Therefore, the exploration of efficient and highly stable electrocatalysts are crucial to accelerate the development of seawater splitting. [29][30][31] Tremendous efforts have been devoted to exploring efficient nonprecious catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Cl − deposition on the cathode surface leads to poor electrode stability and the inferior efficiency of the catalyst. [25][26][27][28] Therefore, the exploration of efficient and highly stable electrocatalysts are crucial to accelerate the development of seawater splitting. [29][30][31] Tremendous efforts have been devoted to exploring efficient nonprecious catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, we have found that Pt single atoms and clusters have a synergistic effect on alkaline HER . Besides, the synergistic catalytic effect of single atoms and clusters or nanoparticles also appears in many other reactions. Therefore, it is of great significance to construct a multi-site catalyst model and reveal the synergistic catalytic mechanism between active sites for the development of high-performance Pt-based acidic HER catalysts and maximizing platinum utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Water splitting to produce hydrogen is a green and environmentally friendly strategy. However, the sluggish kinetic properties of hydrogen evolution reaction (HER) require an efficient catalyst to bridge the gap between the theoretical potential and the actual required potential, that is, to obtain a great current density at a little overpotential [20–21] . The better electrocatalytic performance is achieved by precious metal catalysts such as metallic platinum, but their lack of natural reserves, expensive and unstable, thus greatly limiting their further application in real‐life applications [22–24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the sluggish kinetic properties of hydrogen evolution reaction (HER) require an efficient catalyst to bridge the gap between the theoretical potential and the actual required potential, that is, to obtain a great current density at a little overpotential. [20][21] The better electrocatalytic performance is achieved by precious metal catalysts such as metallic platinum, but their lack of natural reserves, expensive and unstable, thus greatly limiting their further application in real-life applications. [22][23][24] Consequently, the development of nonprecious metal-based catalysts that are abundant in nature, low cost, efficient, and with long-term stability is an effective strategy to commercialize clean and green energy.…”
Section: Introductionmentioning
confidence: 99%